Prediction, Diversity, and Genomic Analysis of Temperate Phages Induced From Shiga Toxin-Producing Escherichia coli Strains - Zhang, Yujie; Liao, Yen-Te; Salvador, Alexandra; Sun, Xiaohong; Wu, Vivian C. H. (Frontiers in Microbiology, 2020)
Shiga toxin-producing Escherichia coli (STEC) is a notorious foodborne pathogen containing stx genes located in the sequence region of Shiga toxin (Stx) prophages. Stx prophages, as one of the mobile elements, are involved in the transfer of virulence genes to other strains. However, little is known about the diversity of prophages among STEC strains. The objectives of this study were to predict various prophages from different STEC genomes and to evaluate the effect of different stress factors on Stx prophage induction. Forty bacterial wholegenome sequences of STEC strains obtained from NCBI were used for the prophage prediction using PHASTER webserver. Eight of the STEC strains from different serotypes were subsequently selected to quantify the induction of Stx prophages by various treatments, including antibiotics, temperature, irradiation, and antimicrobial agents. After induction, Stx1-converting phage Lys8385Vzw and Stx2-converting phage Lys12581Vzw were isolated and further confirmed for the presence of stx genes using conventional PCR. Phage morphology was observed by transmission electron microscopy. The prediction results showed an average of 8 to 22 prophages, with one or more encoding stx, were predicted from each STEC genome obtained in this study. Additionally, the phylogenetic analysis revealed high genetic diversity of Stx prophages among the 40 STEC genomes. However, the sequences of Stx prophages in the genomes of STEC O45, O111, and O121 strains, in general, shared higher genetic homology than those in other serotypes. Interestingly, most STEC strains with two or more stx genes carried at least one each of Stx1 and Stx2 prophages. The induction results indicated Stx1 and Stx2 prophages from the 8 selected STECs were prone to be induced by EDTA and UV, respectively. Additionally, both Stx-converting phages could infect non-pathogenic E. coli (WG5, DH5α, and MG1655) and form new lysogens. The findings of this study indicate that Stx prophages can be induced by environmental stress, such as exposure to solar radiation, and pose a risk of virulence gene transfer to other commensal strains.